Peningkatan Pengetahuan Ibu-Ibu Rumah Tangga Dalam Perilaku Pengobatan Sendiri Untuk Penatalaksanaan Demam Dengan Metode Cara Belajar Ibu Aktif: Increased Knowledge of Housewives in Self-Treatment Behavior for Fever Management Using Active Mother’s Ways of Learning Method - Rezqi Handayani (Borneo Journal of Pharmacy, 2018)
Pharmacological therapy in fever patients is to provide Antipyretic drugs, can be done by using a doctor's prescription or by self-treatment. The condition that occurs in the community is self-medication conducted in the category of irrational treatment therapy because it is not in accordance with the condition of the patient. So, it is necessary to do education using Active Mother’s Ways of Learning Method to the housewives about rational fever self-treatment. The sample in this study were 40 housewives in the Flamboyant Bawah, divided into two major groups namely the control and treatment groups. Each group was given a pretest and posttest in a questionnaire of fever management. In the treatment group, fever drug education given before posttest by used CBIA method. The results showed an increase in knowledge of housewives from before education and after education was seen from the acquisition of grades. The mean pretest value in the control group was 74.38 and the treatment group was 69.69. Statistical test results show there was no significant difference in the mean value between the control group and the treatment group. The mean posttest value in the control group was 77.81 and the treatment group was 87.50. There was a significant difference between the mean value of the control group and treatment group. From the results of the statistical analysis showed that the level of knowledge of the treatment group given education by used the CBIA method produced a higher value than the control group that was not given education.